2011
DOI: 10.1242/dev.061507
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal subtype specification in the spinal cord of a protovertebrate

Abstract: There was an error published in Development 138, 995-1004.On p. 1000, it was incorrectly stated that Islet can repress Vsx in A13.474 but not in A11.117. The reverse is true, as stated in the legend to Fig. 6B. The corrected text appears below.Vsx can actually induce ectopic Islet expression (Fig. 6C), while Islet can repress Vsx in A11.117, but not in A13.474 (Fig. 6B), hinting at a more complicated interaction between these two genes.The authors apologise to readers for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 67 publications
7
77
0
Order By: Relevance
“…For example, we showed that FGF signaling is upstream of vsx2 during zebrafish retinal neurogenesis, as has been demonstrated in mouse RPCs Horsford et al, 2005). Moreover, our data indicate that vsx2 and dmbx1 function in an antagonistic manner in embryonic RPCs, similar to their homologs in Ciona that act to promote different types of motor ganglion interneurons from posterior neural tube progenitor cells (Stolfi and Levine, 2011). However, our findings also reveal novel insight into the regulation of this signaling axis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For example, we showed that FGF signaling is upstream of vsx2 during zebrafish retinal neurogenesis, as has been demonstrated in mouse RPCs Horsford et al, 2005). Moreover, our data indicate that vsx2 and dmbx1 function in an antagonistic manner in embryonic RPCs, similar to their homologs in Ciona that act to promote different types of motor ganglion interneurons from posterior neural tube progenitor cells (Stolfi and Levine, 2011). However, our findings also reveal novel insight into the regulation of this signaling axis.…”
Section: Discussionsupporting
confidence: 78%
“…As the proposed function for dmbx1 is to promote RPC cell cycle exit and differentiation cell-autonomously, we hypothesized that these two genes might function antagonistically during retinogenesis. Consistent with this notion, it has been reported that Dmbx1 and Vsx2 strongly repress each other during visceral ganglion cell fate specification in Ciona (Stolfi and Levine, 2011). Normally the expression of vsx2 is sharply down-regulated in the central retina at $48 hpf, coincident with the onset of dmbx1 expression (Chang et al, 2006).…”
Section: Dmbx1 Functions Cell Autonomously To Regulate Rpc Behaviorsupporting
confidence: 55%
“…The VAChT- positive MN outside the lineage was not affected by FGF8/17/18>COE::WRPW since it does not express FGF8/17/18 . Electroporation of FGF8/17/18>Ets::WRPW 43 converts the entire A9.30 lineage into cholinergic neurons, as predicted 44 , demonstrating the specificity of the COE::WRPW effect. Scale bar, 50μm.…”
Section: Figuresupporting
confidence: 62%
“…This fragment was cloned upstream of unc-76-tagged Venus (YFP). COE>mCherry and FGF8/17/18>H2B::mCherry have been previously described 44 . HA-tagged COE::WRPW 35 and Ets::WRPW 43 coding sequences were subcloned downstream of FGF8/17/18 driver in place of H2B::mCherry to make FGF8/17/18>COE::WRPW and FGF8/17/18>Ets::WRPW, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…5B). A/A n 10.57 also displayed a more elongated shape along its anterior-posterior axis than the other perimeter cells (Imai and Meinertzhagen, 2007a;Okada et al, 2002;Stolfi and Levine, 2011). Using these morphological landmarks, we could find the borders between the neck, VG, and caudal NT (Fig.…”
Section: Sensory Vesicle (Sv)mentioning
confidence: 87%